Effects of slight ski boot weight variations on ski mountaineering energy cost and mechanical work at race intensity - Bortolan, L.; Savoldelli, A.; Fornasiero, A.; Nanni, S.; Gazzi, L.; Decet, M.; Zoppirolli, C.; Schena, F.; Pellegrini, B. (Sport Sciences for Health, 2024)
Purpose Uphill ski mountaineering performance appears to be related to metabolic cost of locomotion and skiers` weight. The present study aimed to evaluate the effects of slight variations in equipment weight on metabolic and mechanical work (MW) of ski mountaineering, at race pace.